Reduced Susceptibility of Plasmodium falciparum to Artesunate in Southern Myanmar - Kyaw, Myat P.; Nyunt, Myat H.; Chit, Khin; Aye, Moe M.; Aye, Kyin H.; Lindegardh, Niklas; Tarning, Joel; Imwong, Mallika; Jacob, Christopher G.; Rasmussen, Charlotte; Perin, Jamie; Ringwald, Pascal; et al. (PloS one, 2013)
Plasmodium falciparum resistance to artemisinins, the first line treatment for malaria worldwide, has been reported in western Cambodia. Resistance is characterized by significantly delayed clearance of parasites following artemisinin treatment. Artemisinin resistance has not previously been reported in Myanmar, which has the highest falciparum malaria burden among Southeast Asian countries. A non-randomized, single-arm, open-label clinical trial of artesunate monotherapy (4 mg/kg daily for seven days) was conducted in adults with acute blood-smear positive P. falciparum malaria in Kawthaung, southern Myanmar. Parasite density was measured every 12 hours until two consecutive negative smears were obtained. Participants were followed weekly at the study clinic for three additional weeks. Co-primary endpoints included parasite clearance time (the time required for complete clearance of initial parasitemia), parasite clearance half-life (the time required for parasitemia to decrease by 50% based on the linear portion of the parasite clearance slope), and detectable parasitemia 72 hours after commencement of artesunate treatment. Drug pharmacokinetics were measured to rule out delayed clearance due to suboptimal drug levels. The median (range) parasite clearance half-life and time were 4.8 (2.1-9.7) and 60 (24-96) hours, respectively. The frequency distributions of parasite clearance half-life and time were bimodal, with very slow parasite clearance characteristic of the slowest-clearing Cambodian parasites (half-life longer than 6.2 hours) in approximately 1/3 of infections. Fourteen of 52 participants (26.9%) had a measurable parasitemia 72 hours after initiating artesunate treatment. Parasite clearance was not associated with drug pharmacokinetics. A subset of P. falciparum infections in southern Myanmar displayed markedly delayed clearance following artemisinin treatment, suggesting either emergence of artemisinin resistance in southern Myanmar or spread to this location from its site of origin in western Cambodia. Resistance containment efforts are underway in Myanmar. Australian New Zealand Clinical Trials Registry ACTRN12610000896077.